Portfolio Selection with Subsistence Consumption Constraints and CARA Utility. (16th April 2014) - Shim, Gyoocheol; Shin, Yong Hyun
Abstract : We consider the optimal consumption and portfolio choice problem with constant absolute risk aversion (CARA) utility and a subsistence consumption constraint. A subsistence consumption constraint means there exists a positive constant minimum level for the agent's optimal consumption. We use the dynamic programming approach to solve the optimization problem and also give the verification theorem. We illustrate the effects of the subsistence consumption constraint on the optimal consumption and portfolio choice rules by the numerical results.